INTEGRASI GREEN HUMAN RESOURCE MANAGEMENT DAN DIGITALISASI DALAM MENDUKUNG PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Nurhaeni Sikki; Nur Setya Oktaviani, Regita; Made Yusadana; Anta Maulana; Dama Riskia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the integration of Green Human Resource Management (GHRM) and digitalization in supporting the achievement of Sustainable Development Goals (SDGs). The increasing global challenges related to environmental degradation and sustainable development require organizations to adopt strategic human resource practices that are not only environmentally oriented but also supported by digital transformation. This research employs a Systematic Literature Review (SLR) approach based on the PRISMA framework to identify, screen, and synthesize relevant studies on GHRM, digital human resource management, sustainability, and SDGs. Data were collected from reputable academic databases and analyzed using thematic analysis to explore key patterns and relationships among variables. The findings indicate that GHRM significantly contributes to improving pro-environmental behavior, organizational environmental performance, and sustainability outcomes. Meanwhile, digitalization functions as an enabling factor that enhances the effectiveness of GHRM implementation through technologies such as HRIS, e-recruitment, e-learning, and paperless systems. The synthesis further reveals that the integration of GHRM and digitalization creates synergistic effects by improving operational efficiency, strengthening employee environmental awareness, and supporting sustainable organizational practices. In addition, this integration contributes to the achievement of SDGs, particularly SDG 8, SDG 9, SDG 12, and SDG 13. However, existing literature still largely treats GHRM and digitalization as separate constructs, indicating a research gap in their integrated application. This study concludes that the integration of GHRM and digitalization serves as a strategic approach to enhancing organizational sustainability and accelerating the achievement of SDGs.